Heritability of sting characters in Africanized honeybees - Melo, A.; Malaspina, O.; Diniz-Filho, J. A. F. (FapUNIFESP (SciELO), 1997)
In this paper we proposed to estimate the heritability of seven morphological characters that compose the sting apparatus ofthe Africanized honeybee workers. An experimental design to estimate genetic parameters was based on the method developed by Oldroyd and Moran. This method was modified to eliminate within-colony environmental effects associated with the additive genetic variance. The estimated h2 values ranged from 0.17 ± 0.11 (maximum width of bulb of sting stylet and height of the valve of right lancet) to 0.74 ± 0.30 (length of the lancet).
Keywords: Apis mellifera; Heritability; Honeybees; Sting; bee sting; heritability; honeybee